EFFECTIVENESS OF PROSTAGLANDIN F2? TO INDUCING HEAT AND CONCEPTION RATE IN BALI CATTLE ANESTRUS POSTPARTUM - Kertawirawan, I Putu Agus; Trilaksana, I Gusti Ngurah Bagus; Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2021)
Induction of heat is one of the technologies in the field of reproduction to accelerate the appearance of heat in cattle. Many methods are used to induction of heat, one of them is by giving prostaglandin F2?. This study aims to determine the effectiveness of the administration of PGF2?  in bali cattle anestrus postpartum with corpus luteum functioning and different body weights to induce the appearance of heat, non-return rate, and conception rate after insemination once and twice at 12-hour intervals. This research was conducted using a randomized block design based on body weight and the number of insemination. Group I (P1) is a group with a bodyweight of less than 250 kg and received one insemination when the appearance of lust, Group II (P2) with a bodyweight of less than 250 kg and received two inseminations at 12-hour intervals, group III (P3) with body weights above 250 kg with one insemination and group IV (P4) with body weights above 250 kg and received twice insemination at 12-hour intervals.  Statistical analysis and testing are done by the analysis of variance. The results showed that the administration of PGF2? caused the emergence of estrus in all experimental animals and there was no significant difference (P> 0.05) to the appearance of heat between the four treatment groups, and the insemination treatment twice intervals 12 hours also had no significant effect to enhance the number of non-return rate and conception rate.